The Phase of Aggressive Behavior, Deprivation among the Inmates Age Group of Nigerian Prisons: A Survey of Sokoto Central Prison. - Ibrahim Yusuf (Universitas Ahmad Dahlan, 2016)
Abstract The article examines the phase of aggressive behavior, deprivation, among the inmate's age group of Nigerian prison. However, the study elaborated the meaning of aggressive behavior; factors contributed to aggressive behavior, theory of aggressive behavior, literature review, method of information collection and data analysis. Therefore, prison setting can instigate aggressive behaviors, especially in Nigeria, where inmates are deprived of their particular right and are treated brutality in some instances studies shows, that Nigerian prisons are not adequately organized and made do as such, inmates are exposed to all kinds of atrocity. It should be noted that a condition of privation and lack of societal well-being especially among people being in an isolated environment as in the case with most prisons in Nigeria can degenerate to frustration and aggression which in turn can result in dangerous situations such as riots/ violence in the prisons. Aggression can lead to violence that may be adaptive under certain conditions regarding natural selection. That is most obviously the case regarding attacking prey to obtain food, or in anti-predator defense. The results showed that there is significant difference between the levels of aggressiveness with respect to the classes of age groups. Recommendation will be discussed further.Keywords: Aggressive behavior, inmates, wardens, phase, and recommendation